Sensitization to gliadin induces moderate enteropathy and insulitis in nonobese Diabetic-DQ8 mice - Galipeau, Heather J. (2011)
Celiac Disease (CD) is frequently diagnosed in patients with type 1 diabetes (T1D), and T1D patients can exhibit antibodies against tissue transglutaminase, the auto-antigen in CD. Thus, gliadin, the trigger in CD, has been suggested to play a role in T1D pathogenesis. The objective of this study was to investigate whether gliadin contributes to enteropathy and insulitis in NOD-DQ8 mice, an animal model that does not spontaneously develop T1D. Gliadin-sensitized NOD-DQ8 mice developed mucosal dysfunction, but no insulitis. Administration of anti-CD25 mAbs before sensitization induced partial depletion of CD25+Foxp3+ T-cells and led to insulitis. Mice that developed insulitis had increased pro-inflammatory cytokines in the mesenteric (MLN) and pancreatic lymph nodes (PLN). CD4+ T-cells isolated from PLN of mice that developed insulitis showed increased proliferation and proinflammatory cytokines after incubations with gliadin but not, with bovine serum albumin (BSA). In control mice, CD4+ T-cells from PLN did not proliferate in response to gliadin. In conclusion, gliadin sensitization induced moderate enteropathy in NOD-DQ8 mice but insulitis development required gliadin-sensitization and partial systemic depletion of CD25+Foxp3+ T-cells. This animal model provides a mechanistic link through which the dietary antigen gliadin, which triggers CD, modulates the onset of insulitis in the presence of partial regulatory T cell deficiency. Both innate and adaptive immune mechanisms related to gluten intolerance can be investigated in NOD-DQ8 mice.